2013
DOI: 10.2494/photopolymer.26.673
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Resist Family Outgassing Characterization between EUV and EB

Abstract: Witness-sample (WS) testing is the most favorable method for the simulation of EUV optics contamination by resist outgassing. Resists are expected to be correctly qualified with this method before they are used in HVM exposure tools. However, the present capacity of outgassing test facilities is insufficient for the total anticipated needs, based on the current capacity of existing EUV exposure tools. This paper defines a resist family for reducing the total number of required outgassing tests. The material co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…13 Although outgassing has received a great deal of attention due to its impact on throughput and damages to optics, only several studies have been reported regarding chemistry of outgassing. [19][20][21][22][23] There have been only one report that deals with influence of Ea on outgassing. 23 Therefore, we have investigated, in particular, effects of Ea on outgassing using a wide variety of polymers with a different acid labile groups (ALG).…”
Section: Outgassing Issue Of Low Ea Polymermentioning
confidence: 95%
“…13 Although outgassing has received a great deal of attention due to its impact on throughput and damages to optics, only several studies have been reported regarding chemistry of outgassing. [19][20][21][22][23] There have been only one report that deals with influence of Ea on outgassing. 23 Therefore, we have investigated, in particular, effects of Ea on outgassing using a wide variety of polymers with a different acid labile groups (ALG).…”
Section: Outgassing Issue Of Low Ea Polymermentioning
confidence: 95%
“…Moreover, we studied noncleanable contamination on the unexposed area and clarified its dependency on the geometry of the WS in the vacuum chamber [3][4][5][6]. Moreover the comparison of the cleanable and noncleanable contamination in the resist family, which consisted of the same components with various protecting ratios and PAG loading, showed a good correlation [7,8]. However, the comparison of noncleanable contamination for resists with various components is not sufficient.…”
Section: Introductionmentioning
confidence: 97%
“…One of the outgas testers used EUV light to expose the resist and WS. The other outgas tester used e-beams for the exposure of resist and WS, and it was named as EUVOM-9000 (Litho Tech Japan Corp.) [6][7][8]. The EUV type tester named HERC was developed for basic outgassing research and not for the resist qualification inorder to avoid the exposure in the scanner.…”
Section: Introductionmentioning
confidence: 99%